ROLE OF DNA METHYLATION AS A DIAGNOSTIC BIOMARKER OF SPORADIC BREAST CANCER - Wirsma Arif Harahap (Journal of the Medical Sciences (Berkala Ilmu Kedokteran), 2016)
The initiation and progression of breast cancer have been recognized for many years to be secondary to the accumulation of genetic mutations which lead to aberrant cellular function. Genetic mutations, either inherited or sporadic, may result in the activation of oncogenes and the inactivation of tumor suppressor genes. The more recent discovery that reversible alterations in histone proteins and deoxyribonucleic acid (DNA) can also lead to tumorigenesis has introduced a novel term to the field of cancer research: epigenetics.  Epigenetics refers to the study of heritable changes in gene regulation that do not involve a change in the DNA sequence. The most often studied in epigenetics of breast cancer is DNA methylation. That a promoter methylation result in transcription blockade supports the notion that cellular inhibition takes place. Compared to normal tissues, hypermethylation occurs from double to triple in cancerous ones. DNA methylation plays a crucial role in oncogenesis and is one of the hallmarks of cancer.Detection of aberrantly methylated CpG islands in promoter region of several genes in DNA sample derived from nipple aspirates, serum, or cancer tissue associated with down regulation of expression or loss of function of these genes has been associated with early stages of breast cancer, where  hypermethylation of CpG island points to poorer prognosis in breast cancer.  DNA methylation has been identified as signature for TNBC. Methylation of BRCA1 gene is frequently demonstrated in young, estrogen receptor-negative breast cancer patients. Methylation of specific genes is known to differ across race and socioeconomic status. BRCA1 methylation in premenopausal women with sporadic breast cancer in West Sumatra region has been higher than in Western women.DNA methylation may be used to enhance current breast cancer classification. There is such a distinction between methylation and gene expression profiles of breast cancer that not all methylation profiles fit within the same molecular subtype. Specific gene methylation profiles are identified for basal-like, luminal A and HER2-overexpressing breast cancers. A number of studies have analyzed the methylation status of BRCA1, a key player in TNBC. One study demonstrated that BRCA1 promoter was methylated in TNBC.  It was discovered that the sensitivity of TNBC cell lines to PARP inhibitors was increased when BRCA1 was methylated. Concurrently, BRCA1 methylation quantity was higher in patients with complete response than in those who are non-responders of neoadjuvant chemotherapy.Epigenetics is now the cutting edge of cancer research.  Advances in this field will have major implications in diagnosis, prevention, treatment of cancer, and formulation of new epigenetically targeted cancer drugs.